An Innate Color Preference Displayed by Xenopus Tadpoles Is Persistent and Requires the Tegmentum - Hunt, Jasper Elan; Bruno, John Rudolph; Pratt, Kara Geo (Frontiers in Behavioral Neuroscience, 2020)
Many animals, especially those that develop externally, are equipped with innate color preferences that promote survival. For example, Xenopus tadpoles are known to phototax most robustly towards mid-spectrum (“green”) wavelengths of light while avoiding shorter (“blue”) wavelengths. The innate preference to phototax towards green likely promotes survival by guiding the tadpoles to green aquatic plants – their source of both food and safety. Here, we characterize the dynamics and circuitry that give rise to this intriguing hard-wired behavior. Using a novel open-field experimental paradigm we found that free-swimming tadpoles indeed spend most of their time in the green portion of the test dish, whether green is pitted against white (brighter than green) or black (darker than green). This preference was modest yet incredibly persistent over time, which, according to the shell game model of predator-prey interactions, minimizes being found by the predator. Furthermore, we found that this innate preference for the color green was experience-independent, and manifested mainly via profoundly slower swimming speeds while in the green region of the test dish. Ablation experiments showed that, at the circuit level, the color-guided swimming behavior requires the tegmentum, but not the optic tectum. Lastly, we determined that exposing tadpoles to the selective serotonin reuptake inhibitor trazodone switched the tadpoles’ preference from color-based to luminance-based, implicating two distinct visual circuits in the tadpole, one that is associated with color-driven behaviors, another associated with luminance-driven behaviors.